Analisis Pengendalian Internal Persediaan Barang Dagang di Toko Bangunan Jaya Perkasa - Dina Margareta; Yuli Nurhayati; Arisky Andrinaldo (Jurnal Pajak dan Analisis Ekonomi Syariah, 2026)
This research was conducted at Toko Bangunan Jaya Perkasa. The purpose of this study is to determine whether the internal control system for inventory management in the observed company has been implemented effectively or not. This study uses a qualitative method with data source triangulation techniques, including observation, interviews, and documentation based on data collection and relevant facts. The research informants consisted of seven individuals. The results show that the internal control system at Toko Bangunan Jaya Perkasa has not been implemented optimally, and the inventory management is still vulnerable to risks and potential losses. This is due to the fact that the procedures for purchasing, storing, recording, and selling goods are still conducted manually. The company faces several problems such as stock discrepancies, damaged goods, and obstacles related to suppliers and customers. The suggestions provided include implementing a computerized system for inventory management in the future, conducting regular stock opname to minimize stock discrepancies, improving communication to avoid duplicate stock records, and establishing clear communication and agreements at the beginning of transactions to overcome external constraints.